"Transcription physiology" of pigment formation in melanocytes: central role of MITF - Vachtenheim, Jiri; Borovanský, Jan (Experimental dermatology, 2010)
Melanin production is the primary mechanism protecting human skin against the UV light-induced damage. The polymeric compound melanin is synthesized within melanocytes in the specialized subcellular organelles, termed melanosomes, which are then transferred to surrounding keratinocytes. The genes for melanin synthesis and deposition are coordinately expressed in melanocytes. The transcription factor MITF, which has been reported to activate more than 25 genes in pigment cells, has emerged as an essential regulator not only for melanocyte development, proliferation and survival, but also for the expression of enzymes and structural proteins ensuring the production of melanin. MITF is a transcriptional activator of several genes which encode melanosome-localized proteins involved both in melanin synthesis and in melanosome biogenesis and transport, including genes whose mutations are associated with human oculocutaneous and ocular forms of albinism. Here, we outline the mechanisms of transcriptional regulation of genes associated with the biosynthesis of melanin in melanocytes and melanoma cells. MITF is crucial in this process, while several other factors seem to have only an auxiliary role to play under specific circumstances.
Keywords: pigmentace kůže; trans-aktivátory; Melanoma; Skin Pigmentation; Stress, Physiological; Promoter Regions, Genetic; Melanocytes; fyziologický stres; Trans-Activators; Melanosomes; Melanins; Models, Biological; Base Sequence; sekvence nukleotidů; melanozomy; Microphthalmia-Associated Transcription Factor; melanom; zvířata; Humans; biologické modely; promotorové oblasti (genetika); melaniny; transkripční faktor spojený s mikroftalmií; lidé; melanocyty; Animals